Avaliação do potencial neuroprotetor da taurina em fenótipos comportamentais e neuroendócrinos associados à esquizofrenia em peixes-zebra - Franscescon, Francini (2022)
Schizophrenia is a chronic neuropsychiatric disease that comprises a complex set of symptoms, which represent a challenge for its study. One of the main experimental strategies for obtaining phenotypes related to schizophrenia involves the use of dizocilpine (MK-801), which is an antagonist of N-methyl-D-aspartate (NMDA) glutamatergic receptors. In the field of neuropsychiatry, several studies have been carried out to find potentially neuroprotective molecules that can prevent the effects of MK-801. Taurine is a sulfur-containing β-amino acid which plays a multifunctional role in the central nervous system (CNS), being considered a neuroprotective molecule. In this work, we analyze the neuroprotective potential of taurine in behavioral and neuroendocrine phenotypes associated with schizophrenia in zebrafish model. Thus, the neuroprotective role of taurine was evaluated against changes in different behavioral domains altered by MK-801 in zebrafish. In the first article, we initially tested the effects of different doses of MK-801 (0.1, 0.3, 0.5, 1 and 2 mg/kg), showing that 2 mg/kg MK-801 was able to replicate behavioral changes (e.g., hyperlocomotion and cognitive impairment) previously reported in the literature. It was shown that taurine pretreatment (42 and 150 mg/L) prevented MK-801-induced cognitive impairment on inhibitory avoidance task. Furthermore, 400 mg/L taurine prevented hyperlocomotion and changes in vertical exploration triggered by MK-801 in the novel tank test. In the second study, we investigated the effect of taurine and MK-801 on social behavior and cortisol levels. In this case, it was observed that taurine pretreatment prevented the disruption of the shoal area, thus restoring in part the alterations in the sociability induced by MK-801. Regarding cortisol levels, 400 mg/L taurine pretreatment abolished MK-801-induced reduction whole-body cortisol levels. In conclusion, the neuroprotective role of taurine in schizophrenia-like phenotypes in zebrafish was highlighted, being taurine effects dependent on the concentration tested and of the phenotype evaluated. However, our results reinforce the suitability of zebrafish to investigate neuroprotective substances with potential to reduce glutamate excitotoxicity in translational neuroscience research.